Influence of fetal birth weight on caesarean section rate and fetal outcome after induction of labor - Temerinac, Dunja; Sütterlin, Marc; Kehl, Sven (In vivo, 2015)
Aim: The aim of the present study was to provide information for better obstetric counselling by analyzing the impact of fetal birth weight on the caesarean section rate and fetal outcome after induction of labor. Materials and Methods: In this retrospective study from January 2010 to December 2013, 1,474 singleton deliveries with labor induction at or greater than 37 gestational weeks were analyzed for their impact of fetal birth weight on delivery outcome. The normal birth weight group was defined as 2,500 g to less than 4,000 g. For comparison, further birth weight groups were defined as: group 1 <2,500 g, group 2 4,000 to <4,250 g; group 3 ≥4,250 g. The primary outcome was the caesarean section rate; secondary outcome measures were fetal complications monitored by pH and base excess (BE) of the umbilical cord artery, Apgar score after 5 min (Apgar-5) and postpartum transfer to the Neonatal Care Unit. The set of controlling variables included maternal body mass index and age, gestational age, neonatal sex, maternal diabetes, maternal hypertension disorder, parity and method of induction of labor. Results: Second-stage caesarean section is significantly more likely when fetal birth weight is below 2,500 g (42.9% vs. 24.2% in the normal birth weight group, odds ratio=3.11, 95% confidence interval=1.48-6.51, p=0.003). A birth weight of 4,000 g or more did not have a significant influence on the caesarean section rate. Only the mean Apgar-5 for group 1 was significantly lower (p=0.044). The non-parametric tests and regression analyzes of pH and BE of the umbilical cord and of the Apgar-5 for adverse fetal outcome (pH<7.05, BE<−12 or Apgar-5 <7) showed no significant differences in the three birth weight groups when compared to the normal group. Neonates were significantly more often transferred to the Neonatal Care Unit after delivery when birth weight was below 2,500 g (odds ratio=9.68, 95% confidence interval=4.33-21.65, p<0.001) or above 4,250 g (odds ratio=2.68, 95% confidence interval=1.34-5.36, p=0.005). Conclusion: Although a fetal birth weight of under 2500 g and a birth weight over 4,250 g are associated with some risks, there is no general contraindication against performing induction of labor in regards to fetal birth weight.